The arcuate nucleus and NPY contribute to the antitumorigenic effect of calorie restriction - Minor, Robin K. (2011)
Calorie restriction (CR) is known to have profound effects on tumor incidence. A typical consequence of CR is hunger, and we hypothesized that the neuroendocrine response to CR might in part mediate CR's antitumor effects. We tested CR under appetite suppression using two models: neuropeptide Y (NPY) knockout mice and monosodium glutamate (MSG)-injected mice. While CR was protective in control mice challenged with a two-stage skin carcinogenesis model, papilloma development was neither delayed nor reduced by CR in the MSG-treated and NPY knockout mice. Adiponectin levels were also not increased by CR in the appetite-suppressed mice. We propose that some of CR’s beneficial effects cannot be separated from those imposed on appetite, and that NPY neurons in the arcuate nucleus of the hypothalamus (ARC) are involved in the translation of reduced intake to downstream physiological and functional benefits.